Monosynaptic Projections to Excitatory and Inhibitory preBötzinger Complex Neurons - Yang, Cindy F.; Kim, Euiseok J.; Callaway, Edward M.; Feldman, Jack L. (Frontiers in Neuroanatomy, 2020)
The key driver of breathing rhythm is the preBotzinger Complex (preBotC) whose activity is modulated by various categorical inputs, e.g., volitional, physiological, emotional. While the preBötC is highly interconnected with other regions of the breathing central pattern generator (bCPG) in the brainstem, there is no data about the direct projections to either excitatory and inhibitory preBotC subpopulations from other elements of bCPG or from suprapontine regions. Using modified rabies tracing, we identified neurons throughout the brain that send monosynaptic projections to identified excitatory and inhibitory preBötC neurons. Within the brainstem, neurons from sites in the bCPG, including the contralateral preBötC, Bötzinger Complex (BötC), the nucleus of the solitary tract (NTS), parafacial region (pFL/pFV or RTN/pFRG), parabrachial nuclei, send direct projections to both excitatory and inhibitory preBotC neurons. Suprapontine inputs to the excitatory and inhibitory preBötC neurons include the superior colliculus, red nucleus, amygdala, hypothalamus, and cortex; these projections represent potential direct pathways for volitional, emotional, and physiological control of breathing.